Effect of Polycondensation Temperature to Oligomer yield and Depolimerisation Side Reaction - Rahmayetty, Rahmayetty; Sukirno, Sukirno; Gozan, Misri (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2018)
Ring-opening polymerization reaction is the best method for producing high molecular weight polymers. The stage of manufacture of PLA from lactic acid through the lactide ring opening reaction is carried out through three stages of the process ie polycondensation, depolymerization and polymerization. The polycondensation stage of lactic acid is the stage of oligomer formation. At the polycondensation stage, the oligomeric molecular weight is determined by the temperature, pressure, type and concentration of the catalyst used. The purpose of this research was to obtain the effect of polycondensation temperature without catalyst on oligomer recovery and side reactions of depolymerization. Polycondensation is done by pretreatment of lactic acid at 120oC for 1 hour. After that, the heating lactic acid at varying temperatures..OLLA yield at polycondensation temperature 150; 180; 200oC for 4 h and gradually (at 150 oC for 2 h and 180oC for 2 h) were 96.33; 85.36; 82.13 and 88.37% respectively. The higher polycondensation temperature, the intramolecular interactions of the molecule as a side reaction was increasing.